Pleistocene megafauna coprolite analysis: inferences about dietary habits and vegetation in a highland ecosystem of South America - Nadia J. Velázquez; M. Eugenia Mosca Torres; Romina S. Petrigh; M. Laura Benvenuto; M. Fernanda Rodríguez; Federico M. Bobillo; Lidia S. Burry; Jorge G. Martínez; Carlos A. Aschero (Quaternary Science Reviews, 2026)

Pesticide removal by fluvial biofilms in lowland streams under different land uses and agricultural seasons - M. A. Mujica; E. De Gerónimo; A. Mosca; S. L. Fanelli; A. H. Paracampo; J. Cochero (International Journal of Environmental Science and Technology, 2026)

Cutaneous apocrine gland neoplasia in 16 captive African wild dogs (Lycaon pictus) - Emily P. Mitchell; Melanie S. Henker; Karin Lemberger; Christine Gohl; Monir Majzoub-Altweck; Almuth Falkenau; Peter Caldwell; Baptiste Chenet; Marion Mosca; Didier Pin; Daniela Denk (Journal of Comparative Pathology, 2023)

The 2020 national seismic hazard model for the United Kingdom - I. Mosca; S. Sargeant; B. Baptie; R. M. W. Musson; T. C. Pharaoh (Bulletin of Earthquake Engineering, 2022)
We present updated seismic hazard maps for the United Kingdom (UK) intended for use with the National Annex for the revised edition of Eurocode 8. The last national maps for the UK were produced by Musson and Sargeant (Eurocode 8 seismic hazard zoning maps for the UK. British Geological Survey Report CR/07/125, United Kingdom, 2007). The updated model uses an up-to-date earthquake catalogue for the British Isles, for which the completeness periods have been reassessed, and a modified source model. The hazard model also incorporates some advances in ground motion modelling since 2007, including host-to-target adjustments for the ground motion models selected in the logic tree. For the first time, the new maps are provided for not only peak ground acceleration (PGA) but also spectral acceleration at 0.2 s (SA 0.2s ) and 1.0 s for 5% damping on rock (time-averaged shear wave velocity for the top 30 m Vs30 ≥ 800 m/s) and four return periods, including 475 and 2475 years. The hazard in most of the UK is generally low and increases slightly in North Wales, the England–Wales border region, and western Scotland. A similar spatial variation is observed for PGA and SA 0.2s but the effects are more pronounced for SA 0.2s . Hazard curves, uniform hazard spectra, and disaggregation analysis are calculated for selected sites. The new hazard maps are compared with the previous 2007 national maps and the 2013 European hazard maps (Woessner et al. in Bull Earthq Eng 13:3553–3596, 2015). There is a slight increase in PGA from the 2007 maps to this work; whereas the hazard in the updated maps is lower than indicated by the European maps.

Coupling proximal sensing, seasonal forecasts and crop modelling to optimize nitrogen variable rate application in durum wheat - F. Morari; V. Zanella; S. Gobbo; M. Bindi; L. Sartori; M. Pasqui; G. Mosca; R. Ferrise (Precision Agriculture, 2021)

Second-tier trio exome sequencing after negative solo clinical exome sequencing: an efficient strategy to increase diagnostic yield and decipher molecular bases in undiagnosed developmental disorders - Frederic Tran Mau-Them; Sebastien Moutton; Caroline Racine; Antonio Vitobello; Ange-Line Bruel; Sophie Nambot; Steven A. Kushner; Femke M. S. de Vrij; Daphné Lehalle; Nolwenn Jean-Marçais; François Lecoquierre; Julian Delanne; et al. (Human Genetics, 2020)

Evaluation of the measurement uncertainty in automated long-term sampling of PCDD/PCDFs - M. Vicaretti; G. D’Emilia; S. Mosca; E. Guerriero; M. Rotatori (Environmental Science and Pollution Research, 2013)

Long-term automated sampling of PCDD/PCDF flue gas: current status and critical issues - M. Vicaretti; S. Mosca; E. Guerriero; M. Rotatori (Environmental Science and Pollution Research, 2012)

Concentration of organic micropollutants in the atmosphere of Trieste, Italy - S. Mosca; G. N. Torelli; G. Tramontana; E. Guerriero; M. Rotatori; M. Bianchini (Environmental Science and Pollution Research, 2012)

Field release of genetically marked Azospirillum brasilense in association with Sorghum bicolor L. - M. Basaglia; S. Casella; U. Peruch; S. Poggiolini; T. Vamerali; G. Mosca; J. Vanderleyden; P. De Troch; M.P. Nuti (Plant and Soil, 2003)

Fibrous root turnover and growth in sugar beet (Beta vulgaris var. saccharifera) as affected by nitrogen shortage - T. Vamerali; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 2003)

Analysis of root images from auger sampling with a fast procedure: a case of application to sugar beet - T. Vamerali; M. Guarise; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 2003)

A comparison of root characteristics in relation to nutrient and water stress in two maize hybrids - T. Vamerali; M. Saccomani; S. Bona; G. Mosca; M. Guarise; A. Ganis (Plant and Soil, 2003)

An approach to minirhizotron root image analysis - T. Vamerali; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 1999)